Primary Healthcare Nurses' Views on Digital Healthcare Communication and Continuity of Care: A Deductive and Inductive Content Analysis - Ove Hellzén; Annika Kjällman Alm; Malin Holmström Rising (MDPI AG, 2022)
Primary healthcare in the Western world faces significant functional challenges, resulting in the implementation of digital communication tools. Nurses are key professionals in primary care and focusing on the impact of digital communication and continuity of care in primary care organisations is important. This qualitative descriptive study explores digital communication and continuity of care from primary healthcare nurses' perspective. Data from individual semi-structured interviews with 12 nurses were collected; deductive and inductive content analyses were performed. Three descriptive categories emerged from the deductive (digital communication as interpersonal, information, and management continuities) and inductive ('digital care does not suit everyone', 'new technology is contextually intertwined with daily work', and 'patient-positive aspects of digital information') phases. Additionally, a structural risk of obscuration of patients' needs by the contextual conditions emerged. To ensure digital communication-aligned continuity of care, compatible information technology systems should be developed. Allowing nurses to provide high-quality care based on their own values would enhance person-centred patient care.